Effects of hTERT transfection on the telomere and telomerase of Periplaneta americana cells in vitro - Chenjing Ma; Xian Li; Weifeng Ding; Xin Zhang; Hang Chen; Ying Feng (AMB Express, 2023)
Abstract Telomere and telomerase are crucial factors in cell division and chromosome stability. Telomerase activity in most cells depends on the transcription control by the telomerase reverse transcriptase (TERT). The introduction of an exogenous human TERT (hTERT) in cultured cells could enhance telomerase activity and elongate the lifespan of various cells. Telomere elongation mechanisms vary between insects and are complex and unusual. Whether the use of exogenous hTERT can immortalize primary insect cells remains to be investigated. In this study, we used a recombinant virus expressing hTERT to infect primary cultured cells of Periplaneta americana and evaluated its effects on insect cell immortalization. We found that hTERT was successfully expressed and promoted the growth of P. americana cells, shortening their doubling time. This was due to the ability of hTERT to increase the activity of telomerase in P. americana cells, thus prolonging the telomeres. Our study lays the foundation for understanding the mechanisms of telomere elongation in P. americana, and suggests that the introduction of hTERT into insect cells could be an efficient way to establish certain insect cell lines.